Alkali solution extraction of rice residue protein isolates: Influence of alkali concentration on protein functional, structural properties and lysinoalanine formation. (1st March 2017) - Hou, Furong; Ding, Wenhui; Qu, Wenjuan; Oladejo, Ayobami Olayemi; Xiong, Feng; Zhang, Weiwei; He, Ronghai; Ma, Haile
Highlights: Alkaline concentration above 0.03 M may cause nutrient or safety problems in extraction of rice residue protein. Alkaline extraction may influence functional or structural properties of rice residue protein. The LAL formation depends on the alkali concentration. Abstract: This study evaluated the nutrient property and safety of the rice residue protein isolates (RRPI) product (extracted by different alkali concentrations) by exploring the protein functional, structural properties and lysinoalanine (LAL) formation. The results showed that with the rising of alkali concentration from 0.03 M to 0.15 M, the solubility, emulsifying and foaming properties of RRPI increased at first and then descended. When the alkali concentration was greater than 0.03 M, the RRPI surface hydrophobicity decreased and the content of thiol and disulfide bond, Lys and Cys significantly reduced. By the analysis of HPLC, the content of LAL rose up from 276.08 to 15, 198.07 mg/kg and decreased to 1340.98 mg/kg crude protein when the alkali concentration increased from 0.03 to 0.09 M and until to 0.15 M. These results indicated that RRPI alkaline extraction concentration above 0.03 M may cause severe nutrient or safety problems of protein.